Market Islam in Qur’an Reading Methods in Indonesia: Tradition and the Dynamics of Emerging Diversity - Mubaidi Sulaeman; Moch. Nur Ichwan; Ahmad Rafiq (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2026)
This study examines Qur’anic reading methods in Indonesia, focusing on Kediri, through the framework of Market Islam to investigate how religious authority is reorganized within contemporary Islamic educational markets. Employing a qualitative case-study approach, the research analyzes three Qur’anic learning methods—Jamiati, Al-Faqih, and Yanbu'a—using in-depth interviews, participant observation, and institutional documentation. The findings demonstrate that the circulation of Qur’anic pedagogy depends not only on spiritual legitimacy but also on the interaction between supply-driven authority, embodied in sanad, charismatic religious leadership, and institutional credibility, and demand-driven mechanisms, including standardization, teacher certification, organizational networks, and socially differentiated educational demand. While Jamiati and Al-Faqih remain predominantly supply-driven initiatives developed to address internal pedagogical needs within pesantren, Yanbu'a represents a hybrid configuration that successfully translates sanad-based authority into scalable organizational forms through standardized curricula, formalized instructor training, and extensive inter-pesantren networks. Unlike the dominant Market Islam literature, which largely associates religious markets with urban Muslim middle-class consumerism, the Kediri case demonstrates that the demand for Qur’anic learning methods is also generated through traditional pesantren communities, where religious capital, institutional trust, and collective educational traditions shape pedagogical preferences. This study extends Market Islam scholarship by arguing that the commodification of Qur’anic pedagogy entails not the erosion of religious authority but its organizational reconfiguration through the interaction of charismatic legitimacy, religious capital, and market rationality within contemporary Muslim educational institutions.